2019
DOI: 10.1371/journal.pone.0213290
|View full text |Cite
|
Sign up to set email alerts
|

Molecular epidemiology survey and characterization of human influenza A viruses circulating among Palestinians in East Jerusalem and the West Bank in 2015

Abstract: Frequent typing and molecular characterization of influenza A (IAV) strains are crucial for the identification of circulating subtypes and for the selection of the subtypes’ lineages to be included in the annually prepared vaccine cocktail. We investigated IAV sampled from an underrepresented population from Palestine. 200 nasopharyngeal aspirates (NPA) were collected between February and May of 2015 from Palestinians in East Jerusalem and the West Bank suffering from mild to severe symptoms of upper respirato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 39 publications
1
3
0
Order By: Relevance
“…Recent study conducted in Middle East and North Africa (MENA) reported evolution of seven genogroups ( 33 ). In our study, after 2015, maximum HA gene sequences clustered in 6B genogroup which is similar to the reports published by WHO and other studies ( 33 37 ). Due to antigenic variations, 6B genogroup variants are reported to associate with increased morbidity compared to other genogroup variants ( 4 , 35 ).…”
Section: Discussionsupporting
confidence: 92%
“…Recent study conducted in Middle East and North Africa (MENA) reported evolution of seven genogroups ( 33 ). In our study, after 2015, maximum HA gene sequences clustered in 6B genogroup which is similar to the reports published by WHO and other studies ( 33 37 ). Due to antigenic variations, 6B genogroup variants are reported to associate with increased morbidity compared to other genogroup variants ( 4 , 35 ).…”
Section: Discussionsupporting
confidence: 92%
“…7 A short-period study from February to May 2015 conducted in East Jerusalem and the West Bank revealed that out of 200 patients suffering from upper respiratory infections, 50 were positive for influenza A virus, 48% of which were of A(H1N1)pdm09 subtype and 52% of H3N2 subtype. 8 In 2006, the Egyptian public health authorities established hospital-based influenza surveillance with a network of 13 sentinel sites throughout the country. Data from patients with Severe Acute Respiratory Infection (SARI) hospitalized in three hospitals from January to December 2013 showed that 19% tested positive for influenza virus, 71% of which were seasonal influenza type A virus.…”
Section: Introductionmentioning
confidence: 99%
“…Another study from Iran showed that 14% of ILI cases referred to healthcare centers from 2010 to 2015 were positive for influenza out of which 71% were type A virus 7 . A short‐period study from February to May 2015 conducted in East Jerusalem and the West Bank revealed that out of 200 patients suffering from upper respiratory infections, 50 were positive for influenza A virus, 48% of which were of A(H1N1)pdm09 subtype and 52% of H3N2 subtype 8 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation